Nutrição mineral e toxidez de cádmio em ginseng brasileiro (Pfaffia glomerata (Spreng.) Pedersen) - Skrebsky, Etiane Caldeira (2007)
Pfaffia glomerata (Spreng) Pedersen, also known as Brazilian ginseng, has been used in popular medicine due to its important medicinal qualities. This study aims to characterize the nutrient needs of P. glomerata, (Chapter 1) as well as to assess the tolerance of this plant to high levels of cadmium in the substrate (Chapter 2). P. glomerata plants produced in vitro and acclimatized ex vitro were used as initial material. In Chapter 1, three (3) experiments are described. In the first experiment, under greenhouse conditions, young plants of P. glomerata were cultivated in Paleudalf soil with different treatments for fertilization: control (without fertilization), complete fertilization (with macro and micronutrients) and the individual omissions of N, P, K, Ca, Mg, S and micronutrients (Zn, B, Cu, Fe, Mn and Mo). In the second experiment, in greenhouse, the plants were submitted to twenty-seven (27) treatments of fertilization in complete trifactorial system (3x3x3), represented by a combination of three levels (40, 80 e 120 mg kg-1) of N, P and K in the fertilization, using the same soil as substrate. In the third experiment, under open field conditions, six (6) treatments involving the combination of two levels (50 e 100 kg ha-1) of N, P and K in the fertilization in two periods of cultivation, sixteen (16) and six (6) months, were evaluated respectively. It was observed in the fertilization in the experiment with the missing nutrient technique that the young plants of P. glomerata showed great decrease in biomass growth as well as in the macro and micronutrients by the omission of the nutrients N, K, S and P. In the second experiment, in greenhouse, the production of biomass by different organs of the plant responded differently to the triple interaction of NPK fertilizations, in which the dosages of maximum technical efficiency estimated (DMET) to the fertilizations of N, P and K in the production of total biomass of the plant were 60, 120 and 80 mg kg-1 respectively. In the open field, the NPK fertilization affected the production of biomass of the organs of the plants in different ways in 16 months of cultivation. In order to have a greater accumulation of mineral nutrients in the tissues of P. glomerata and a possible relation to the accumulation of active principles of medicinal interests, the plants should be collected after six (6) months of field cultivation. In the study described in Chapter 2, an experiment with seedlings of Pfaffia glomerata cultivated under the hydroponic system with five levels of cadmium (Cd) (0, 20, 40, 60 e 80 μm) was carried out during seven days. Those plants demonstrated an increase in the content of Cd in the roots and shoots. The total biomass was reduced significantly in 80 μM of Cd. The activity of the ALA-D (delta-aminolevulinic acid dehydratase) and AP (acid phosphatase) was reduced with the levels of Cd. The reduction in the activity of ALA-D was accompanied by the content of chlorophyll. Enzymatic antioxidants, such as catalase and ascorbate peroxidase, as well as non-enzymatic antioxidants like ascorbic acid and non-protein thiol groups had an important role in the detoxification of effects induced by Cd in the roots and shoot of the seedlings of P. glomerata.